Efforts In Conserving Purebred Bali Cattle As Draught And Beef Type In Bali Island, Indonesia. (UPAYA PELESTARIAN SAPI BALI SEBAGAI TABUNGAN DAN TIPE PEDAGING DI PULAU BALI INDONESIA) - Kasa, I Wayan; Sukmaningsih, Anak Agung Sagung; Darmayasa, Ida Bagus (Buletin Veteriner Udayana, 2015)
Bali cattle (Bos javanicus d’Alton) is a part of the complex evolution of all cattle over a longtime in Indonesia. Little is known of the origin of bali cattle in Southeast Asia.  The geographicaldistribution of Bos (Bibos) types of cattle suggests that the centre of domestication was Indo-China and Malaysia, then spreading to Bali. Due to such several unique characters of bali cattle, someefforts have been conducting with main purpose to conserve purebred, draught as well as meat typecattle on Bali in particular and Indonesia in general. Method has been employed in this study areliterature explore, visiting, interview with questionnaire sheet. Set of efforts have been conductingin order to conserve purebred bali cattle by the government. For examples, establishment of balicattle Breeding centre of Pulukan village, establishment of bali cattle Breeding centre of Sobanganvillage, establishment of bali cattle Conservation centre of Nusa Penida Island,  essense of UdayanaUniversity, Bali and role of Department of Animal Husbandry. It could be concluded thatgovernment as a whole have played an important role in conserving the purebred bali cattle asdraught and meat type cattle at certain suitable places in Bali to fulfill local and national daily meatrequirement by establishing good collaboration with related government agency as well as farmers.
Keywords: bali cattle; local government; Bali island; conservation